ICC arbitration in practice - Schäfer, Erik, 1957- (Kluwer Law International, 2016)
The Rules of Arbitration of the International Chamber of Commerce? commonly referred to as the ICC Rules? are the rules most frequently used in commercial disputes between business partners from different countries. Since they were first launched in 1922, these Rules have been applied in over 20,500 cases. The second revised edition of this eminently practical volume provides an article-by-article commentary of the current version of the ICC Rules of Arbitration in force as from 1 January 2012. Using clear and concise language, unencumbered by footnotes and illustrated by flow diagrams, the authors guide the reader through the various stages of ICC arbitration proceedings, from initiation to the final award.